L-type CaV1.2 deletion in the cochlea but not in the brainstem reduces noise vulnerability: implication for CaV1.2-mediated control of cochlear BDNF expression - Zuccotti, Annalisa; Lee, Sze Chim; Campanelli, Dario; Singer, Wibke; Satheesh, Somisetty Venkata; Patriarchi, Tommaso; Geisler, Hyun-Soon; Köpschall, Iris; Rohbock, Karin; Nothwang, Hans Gerd; Hu, Jing; Hell, Johannes W.; et al. (Frontiers in Molecular Neuroscience, 2013)
Voltage-gated L-type Ca2+ channels (L-VGCCs) like CaV1.2 are assumed to play a crucial role for controlling release of trophic peptides including brain-derived neurotrophic factor (BDNF). In the inner ear of the adult mouse, beside the well described L-VGCC CaV1.3, also CaV1.2 is expressed. Due to lethality of constitutive CaV1.2 KO mice, the function of this ion channel as well as its putative relationship to BDNF in the auditory system is entirely elusive. We recently described that BDNF plays a differential role for inner hair cell (IHC) vesicles release in normal and traumatized condition. To elucidate a presumptive role of CaV1.2 during this process, two tissue-specific conditional mouse lines were generated. To distinguish the impact of CaV1.2 on the cochlea from that on feedback loops from higher auditory centers CaV1.2 was deleted, in one mouse line, under the Pax2 promoter (CaV1.2Pax2) leading to a deletion in the spiral ganglion neurons (SGN), dorsal cochlear nucleus (DCN), and inferior colliculus (IC). In the second mouse line, the Egr2 promoter was used for deleting CaV1.2 (CaV1.2Egr2) in auditory brainstem nuclei. In both mouse lines normal hearing threshold and equal number of IHC release sites were observed. We found a slight reduction of auditory brainstem response (ABR) wave I amplitudes in the CaV1.2Pax2 mice but not in the CaV1.2Egr2 mice. After noise exposure, CaV1.2Pax2 mice had less pronounced hearing loss that correlated with maintenance of ribbons in IHCs and less reduced activity in auditory nerve fibers, as well as in higher brain centers at supra-threshold sound stimulation. As reduced cochlear BDNF mRNA levels were found in CaV1.2Pax2 mice, we suggest that a CaV1.2 dependent step may participate in triggering part of the beneficial and deteriorating effects of cochlear BDNF in intact systems and during noise exposure through a pathway that is independent of Cav1.2 function in efferent circuits.